Diabetic Cardiomyopathy: Impact of Biological Sex on Disease Development and Molecular Signatures - Toedebusch, Ryan; Belenchia, Anthony; Pulakat, Lakshmi (Frontiers in Physiology, 2018)
Diabetic cardiomyopathy refers to a unique set of heart-specific pathological variables induced by hyperglycemia and insulin resistance. Given that cardiovascular disease is the leading cause of death in the world, and type 2 diabetes incidence continues to rise, understanding the complex interplay between these two morbidities and developing novel therapeutic strategies is vital. Two hallmark characteristics specific to diabetic cardiomyopathy are diastolic dysfunction and cardiac structural mal-adaptations, arising from cardiac cellular responses to the complex toxicity induced by hyperglycemia with or without hyperinsulinemia. While type 2 diabetes is more prevalent in men compared to women, cardiovascular risk is higher in diabetic women than in diabetic men, suggesting that diabetic women take a steeper path to cardiomyopathy and heart failure. Accumulating evidence from randomized clinical trials indicate that although premenopausal women have lower risk of cardiovascular diseases, compared to age-matched men, this advantage is lost in diabetic pre-menopausal women, which suggests estrogen availability does not protect from increased cardiovascular risk. Notably, few human studies have assessed molecular and cellular mechanisms regarding similarities and differences in the progression of diabetic cardiomyopathy in men versus women. Additionally, most pre-clinical rodent studies fail to include female animals, leaving a void in available data to truly understand the impact of biological sex differences in diabetes-induced dysfunction of cardiovascular cells. Elegant reviews in the past have discussed in detail the roles of estrogen-mediated signaling in cardiovascular protection, sex differences associated with telomerase activity in the heart, and cardiac responses to exercise. In this review, we focus on the emerging cellular and molecular markers that define sex differences in diabetic cardiomyopathy based on the recent clinical and pre-clinical evidence. We also discuss miR-208a, MED13, and AT2R, which may provide new therapeutic targets with hopes to develop novel treatment paradigms to treat diabetic cardiomyopathy uniquely between men and women.